Pengolahan Dendeng Cumi Pada Kelompok UMKM DAFALA Di KotaTernate - Abubakar, Yuyun; Salim Abubakar; Riyadi Subur; sunarti; Rina; Ariyati H. Fadel; Sahlan Norau; Raut Wahyuning Paluphi; Raut Nugrahening Widhi; Disnawati; Adinoman Susanto (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
North Maluku is one of the potential areas for squid fishing, namely in Bobaneigo (Abdulkadir et al. 2022)5 and in Ternate City (Togafo waters and its surroundings). Squid jerky, and processed food products in general, are easily damaged if not stored properly. Many factors can cause damage to squid jerky, both damage due to the process of the food ingredients themselves and factors originating from external influences of food products (Wahyuni ​​and Lasmi., 2023). The objectives of PKM are to provide additional knowledge to partners about the diversification of processed non-fish fishery resources, introduce methods of processing jerky from squid as a raw material, train partners how to process squid into jerky and facilitate participants with the tools and materials needed to produce products (jerky) using squid. The training activity on processing squid jerky by utilizing the potential of squid resources in Togafo Village, West Ternate District went smoothly with high enthusiasm from the participants. The enthusiasm for the results of squid jerky products. Community Service Program activities increase knowledge about non-fish products, improve community skills, and foster entrepreneurial spirit.